Naturally acquired immune responses against Plasmodium falciparum sporozoites and liver infection. - Offeddu, V; Thathy, V; Marsh, K; Matuschewski, K (2012)
Malaria is a vector-borne infectious disease caused by infection with eukaryotic pathogens termed Plasmodium. Epidemiological hallmarks of Plasmodium falciparum malaria are continuous re-infections, over which time the human host may experience several clinical malaria episodes, slow acquisition of partial protection against infection, and its partial decay upon migration away from endemic regions. To overcome the exposure-dependence of naturally acquired immunity and rapidly elicit robust long-term protection are ultimate goals of malaria vaccine development. However, cellular and molecular correlates of naturally acquired immunity against either parasite infection or malarial disease remain elusive. Sero-epidemiological studies consistently suggest that acquired immunity is primarily directed against the asexual blood stages. Here, we review available data on the relationship between immune responses against the Anopheles mosquito-transmitted sporozoite and exo-erythrocytic liver stages and the incidence of malaria. We discuss current limitations and research opportunities, including the identification of additional sporozoite antigens and the use of systematic immune profiling and functional studies in longitudinal cohorts to look for pre-erythrocytic signatures of naturally acquired immunity.